Letter - Gondra, Angel de
025a-0011-001 Euzkadi Ordezkaritza Basque Delegation, 7/8 Hobart Place, Eaton Square, London, S W.1. TEL: SLOANE 4359. 27th December, 1940. A. Carthy, Esq, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Mr. Carthy, With reference to our telephone conversation of the other day regarding the Basque, Juan Expositos, who was a stoker on board the "Baron Blithwood" and was drowned when this ship was sunk recently, I have now discovered that the Shipping Company is Hobart Sons & Co. of 16 St. Helens Place, Bishopsgate, E.C.2. I feel I should pass this information on to you, as I presume that you will be taking the matter up with the shipowners. Juan Expositos belonged to the Sunderland group of Basques, and in the original list he seems to have appeared under the name of "Jose". For my part, I am getting in touch with Sra. Maria Basabe, who was a friend of this men and, I believe, related to him, in order to inform her and to inquire about his family, and I will let you know as soon as I have any further information. Yours sincerely, A. de Gondra, Secretary. 292/946/25a/11